WHEEL OF LIFE: TEACHING SCIENCE THROUGH AN ADAPTED VERSION OF SPIN THE WHEEL GAME - Sidin, Denciscka Ellyvia; Sawadi, Elesta; John, Leslie Liau; Bedesly, Hidayu; Peter, Deassy Souza; Idek, Sirhajwan (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The research attempted to examine a teaching aid designed to teach basic learning skills of recognizing, naming, and describing among preschool children on a science topic. The teaching aid referred to as “Wheel of life” is based on the conventional concept of a board game that allows unpredictability and control. Preschool teachers often find it difficult to get children to pay attention during class and this could hinder them from gaining understanding on how to link different pieces of information and explain them properly in any specific topic. Thus, this research aimed to explore the potential of this game in increasing children’s level of engagement in the lesson to the extent of being able to link different pieces of information. A popular science topic related to life cycles of different animals was chosen since it was one of the most difficult topics to teach in science lessons for preschool children. A group of six children, along with a teacher, was chosen as subjects for this study. There were two research methods: observation through a checklist on the children’s behavioral responses and semi-structured interviews for the parents and teachers. The findings from this research revealed children’s increased level of engagement in the classroom as they challenged themselves to identify the right answers within a competitive yet collaborative atmosphere.